2017
DOI: 10.1136/bjophthalmol-2016-310023
|View full text |Cite
|
Sign up to set email alerts
|

Poppers: legal highs with questionable contents? A case series of poppers maculopathy

Abstract: On the basis of the products tested here, it seems that isopropyl nitrite is toxic to the fovea and can cause significant visual disturbance. The production of poppers is unregulated and their popularity is concerning, particularly given their exemption from the Psychoactive Substances Act 2016, which might suggest that they are harmless chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0
16

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 17 publications
0
28
0
16
Order By: Relevance
“…To date, the exact mechanism of popper toxicity remains unknown. One thought is that alkyl nitrites cause upregulation of nitric oxide, which may increase photoreceptor photosensitivity [1,4,5].This mechanism is corroborated by the fact that both nitrite toxicity and photic damage result in a maculopathy characterized by focal ellipsoid zone disruption or loss on SD-OCT [9].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To date, the exact mechanism of popper toxicity remains unknown. One thought is that alkyl nitrites cause upregulation of nitric oxide, which may increase photoreceptor photosensitivity [1,4,5].This mechanism is corroborated by the fact that both nitrite toxicity and photic damage result in a maculopathy characterized by focal ellipsoid zone disruption or loss on SD-OCT [9].…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports in the literature have documented spontaneous resolution of symptoms and imaging findings over time. Patients had better visual recovery if they abstained from the drug once symptoms began, or if they were taking the drug infrequently or for the first time [4,9]. Pahlitzsch et al [10] described one patient who demonstrated near resolution of the maculopathy following 6 months of oral lutein supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Le mécanisme physiopathologique de l'atteinte maculaire n'est pas connu. L'atteinte spécifique de la fovéa suggère un mécanisme photo-induit que pourrait aggraver la libération aiguë et massive de NO (le NO étant un modulateur physiologique du métabolisme et de la fonction des photorécepteurs) [7]. La fréquence de ces lésions n'est pas connue.…”
Section: Discussionunclassified
“…Il existe vraisemblablement une susceptibilité individuelle. Par ailleurs, la description de cas survenant après un changement de marque chez des consommateurs habituels évoque des différences de toxicité entre les poppers [7].…”
Section: Discussionunclassified
See 1 more Smart Citation